A New Perspective on Education in the Digital Age : Teaching, Media and Bildung - Tække, Jesper; Paulsen, Michael; Baker, Alison; Baker, Alison (Bloomsbury Academic)
Explores a new perspective on education in digital age, drawing together action-based research with sociology of education, medium theory and educational theory, especially the Bildung-tradition.
English
Keywords: Educational equipment & technology, computer-aided learning (CAL)